Aquinas and the virtues of hope: theological and democratic - Lamb, M (Wiley, 2016)
A prominent political historian has recently identified unwarranted optimism and unwarranted pessimism as democracy's “dual dangers.” While this historical analysis highlights the difficulties that accompany democratic hope, our prevailing conceptual vocabulary obscures the resources needed to address them. This essay attempts to recover these resources by excavating insights from Thomas Aquinas, who supplies one of the most systematic accounts of hope in the history of religious and political thought. By appropriating the conceptual structure of Thomas's theological virtue of hope, this essay reconstructs a democratic virtue that perfects acts of hoping in fellow citizens to achieve democratic goods and thereby enables citizens to respond properly to difficulties that tempt presumption and despair.